2016
DOI: 10.21451/1984-3143-ar878
|View full text |Cite
|
Sign up to set email alerts
|

Markers of pregnancy: how early can we detect pregnancies in cattle usingpregnancy-associated glycoproteins (PAGs) and microRNAs?

Abstract: Pregnancy detection has evolved over the last few decades and the importance of early pregnancy detection is critical to minimize the amount of time a cow spends not pregnant. Embryonic mortality (EM) is generally considered to be the primary factor limiting pregnancy rates in cattle and occurs early ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 69 publications
0
12
0
5
Order By: Relevance
“…Early pregnancy detection allows the re-insemination of non-pregnant cows as soon as possible to reduce calving intervals and replace infertile cows. Accurate and early detection of pregnancy is a necessary procedure in livestock management since it assists in reducing open days of cows that failed to conceive, leading to significant economic gains ( 17 ). When a pregnant cow is mistakenly classified as non-pregnant, the stresses caused by treatment and re-insemination might increase the possibility of iatrogenic abortion ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early pregnancy detection allows the re-insemination of non-pregnant cows as soon as possible to reduce calving intervals and replace infertile cows. Accurate and early detection of pregnancy is a necessary procedure in livestock management since it assists in reducing open days of cows that failed to conceive, leading to significant economic gains ( 17 ). When a pregnant cow is mistakenly classified as non-pregnant, the stresses caused by treatment and re-insemination might increase the possibility of iatrogenic abortion ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Limits of both must be considered. Pregnancy diagnosis based on day 31 PAG concentration has been shown to be comparable to accuracy from day 31 ultrasound [30,39,49]. Based on this set of data, the ability to detect nonpregnant animals by PAG concentration at day 24 is variable as evident by the inconclusive predictive cutoff value in both study 1 and 2.…”
Section: Fig 4 Study 2 Day 24 Pag Concentration By Paritymentioning
confidence: 86%
“…Following migration of binucleated trophoblast cells and interdigitation of microvilli on fetal and maternal membranes, PAGs enter the maternal circulation [28,29] and are detectable by a multitude of different assays. Pregnancy diagnosis through detection of PAGs is well established and available commercially in cattle and other ruminants beginning at day 28 of gestation [30]. Pregnancy associated glycoproteins may be detected in circulation of Receiver operating characteristic (ROC) curve was used for predictive value analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the knowledge about the exact number and function of bovine PAG (boPAG) is incomplete [7], but the accumulation and circulation in maternal blood and milk have made boPAG a very useful and important tool for pregnancy diagnosis in cattle [5,[9][10][11][12]. Different studies demonstrated that boPAG can be used as reliable pregnancy markers in serum and milk, applicable as early as approximately day 25 post breeding [5,[13][14][15]. Thus, the detection of boPAG in serum or milk is an alternative method to transrectal ultrasonography or progesterone assays.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, boPAG-determination allows the direct identification of a placental product present in the maternal system that can be used as a marker of a viable pregnancy [ 16 ]. Some studies already figured out that boPAG are effective at identifying cows that will undergo early fetal mortality or late embryonic loss and are potential markers for a healthy placental function [ 15 , 17 , 18 ]. For these reasons, the measurement of boPAG in blood or milk is an important and powerful diagnostic tool for livestock management.…”
Section: Introductionmentioning
confidence: 99%